Financial Channels, Property Rights and Poverty: A Sub‐Saharan African Perspective. (10th May 2016) - Singh, Raju Jan; Huang, Yifei
Abstract : Studies on the link between financial development and poverty have been inconclusive. Some claim that deeper financial sectors should improve the allocation of capital by allowing entrepreneurs greater access to finance, which should particularly favour the poor. Others argue that improvements in the financial system primarily benefit the rich and politically connected. The literature has also been ambiguous about the channels through which finance may be associated with lower poverty (deposits vs. credit). Looking at a sample of 37 countries in sub‐Saharan Africa from 1992 through 2006, the paper suggests that financial deepening is associated with lower poverty through different channels depending on the strength of property rights. In the absence of well‐defined and enforced property rights, wider access to saving and risk‐sharing instruments is accompanied by a reduction in poverty. Only once property rights grow stronger, is credit associated with lower poverty.